2015
DOI: 10.5762/kais.2015.16.11.7754
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Design of an Outer Tie Rod Using Meta-Model Based Optimization Technique

Abstract: The outer tie rod is one of the part of steering system, the optimization process was executed to find the lightweight design. The inner tie rod was considered in the optimum design of an outer tie rod. it could be closer to the test condition than in the case of considering outer tie rod only. The aluminum forging material was considered as a weight reduction proposal. The target of optimization was the shape of the minimum weight to resist at the load of buckling. RSM and Kriging interpolation method were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Furthermore, he also carried out stress analysis on the shape of the tie rod and concluded that a tie rod with square and circular sections is more complex than a tie rod with only a circular shape. Kim et al [24], Navale et al [25], and Wayal et al [26] found that aluminum tie rods were superior to traditional cast-iron tie rods. Kim et al also optimized the shape of aluminum tie rods using the RSM and Kriging interpolation method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, he also carried out stress analysis on the shape of the tie rod and concluded that a tie rod with square and circular sections is more complex than a tie rod with only a circular shape. Kim et al [24], Navale et al [25], and Wayal et al [26] found that aluminum tie rods were superior to traditional cast-iron tie rods. Kim et al also optimized the shape of aluminum tie rods using the RSM and Kriging interpolation method.…”
Section: Introductionmentioning
confidence: 99%